Silica Nanofluids in an Oilfield Polymer Polyacrylamide: Interfacial Properties, Wettability Alteration, and Applications for Chemical Enhanced Oil Recovery - Sharma, T.; Iglauer, Stefan; Sangwai, J. (American Chemical Society, 2016)
Oil production from matured crude oil reservoirs is still associated with low recovery factors. Chemical enhanced oil recovery (EOR) is one of the techniques which can significantly improve the recovery factor of the trapped oil. This is mainly achieved by lowering the interfacial tension (IFT) of the crude oil-brine/aqueous chemical and increasing the viscosity of the injected fluid. Nanofluids have demonstrated potential in this respect, and we thus examined how such nanofluids behave when formulated with standard oilfield polymers, with a particular focus on their EOR efficiency. In this work, silica (SiO2) nanofluids with (NSP) or without (NP) surfactant (sodium dodecyl sulfate) added and with varying nanoparticle concentration were formulated with polyacrylamide (PAM) and characterized by DLS and ?-potential measurements. These nanofluids were then tested in EOR core-flood experiments. Various studies involving the stability and viscosity of nanofluids, interfacial tension of the nanofluid-crude oil system, their effect on wettability alteration, and efficiency for EOR studies as a function of temperature have been reported. The efficiency of the nanofluid systems for IFT reduction and EOR has also been compared with the conventional polymer (P) and surfactant-polymer (SP) flood schemes. The SiO2 nanofluids significantly increased oil recoveries, particularly at higher temperatures, mainly due to IFT reduction, fluid viscosity increase, and wettability alteration (from intermediate-wet to strongly water-wet). We conclude that SiO2 nanofluids can potentially be attractive EOR chemicals, particularly for wettability alteration operations and high temperature applications. © 2016 American Chemical Society